Association of circulating 25-hydroxyvitamin D with time in range and insulin secretion in type 2 diabetes - Jiang, Wenwen; Li, Ling; Wang, Wei; Liang, Yue; Bai, Xiaoyong; Xu, Yixin; Guo, Qingyu; Ge, Lichao; Liang, Jingjing; Lu, Bin; Shao, Jiaqing (Frontiers in Endocrinology, 2025)
BackgroundTo explore the association of circulating 25-hydroxyvitamin D [25(OH)D] with time in range and insulin secretion in type 2 diabetes.Methods911 patients diagnosed with type 2 diabetes mellitus (T2DM) were included, and they underwent 3-day continuous glucose monitoring (CGM) and serum 25(OH)D measurements. The subjects were categorized into three groups based on the tertiles of their serum 25(OH)D levels: G1 (25(OH)D ≤ 21.22 ng/mL), G2 (21.22 ng/mL ≤ 25(OH)D < 26.43 ng/mL), and G3 (25(OH)D ≥ 26.43 ng/mL). TIR and glycemic variability (GV) parameters were evaluated with CGM. Insulin resistance was evaluated via the homeostatic model assessment of insulin resistance (HOMA-IR). The pancreatic β-cell function was determined using the homeostasis model assessment of β-cell function (HOMA-β). Among the 911 enrolled subjects, 582 individuals underwent a 100g standardized steamed bread meal test to comprehensively evaluate the pancreatic β-cell secretory function.ResultsA higher TIR and time in tight range (TITR) were observed among individuals in the upper tertile for 25(OH)D, surpassing those in the middle and lower tertiles. The results of correlation analysis revealed that serum 25(OH)D levels were significantly positively correlated with TIR and TITR. Conversely, serum 25(OH)D levels were negatively associated with time above range, GV parameters, hemoglobin A1c (HbA1c), and HOMA-IR. However, no significant association was observed between serum 25(OH)D levels and HOMA-β. Additionally, the correlation between 25(OH)D and TIR (r=0.217, P<0.001) was slightly stronger than that between 25(OH)D and HbA1c (r=-0.130, P<0.001). Multiple stepwise linear regression analysis indicated that serum 25(OH)D levels were an independent influencing factor for TIR. Among individuals who underwent the steamed bread meal test, serum 25(OH)D exhibited a positive correlation with indicators of early-phase and overall pancreatic β-cell secretion capacity.ConclusionsThis study demonstrated that in patients with T2DM, 25(OH)D levels exhibited positive correlations with TIR and glucose-stimulated insulin secretion parameters, while showing negative correlations with GV parameters. Lower serum 25(OH)D levels may adversely impact glucose homeostasis and pancreatic β-cell secretory function in T2DM patients.